Instagram addiction in teenagers: The role of type D personality, self-esteem, and fear of missing out - Rahardjo, Wahyu; Mulyani, Indah (Psikohumaniora: Jurnal Penelitian Psikologi, 2020)
Instagram addiction is a social phenomenon among teenagers that has been little studied. This study aims to empirically examine the effect of type D personality (social disinhibition and negative affectivity), self-esteem, and fear of missing out (FoMO) on Instagram addiction among adolescents. A total of 259 participants living in Greater Jakarta, Indonesia, with type D personalities with mild to severe addiction were identified through screening results (based on total score). Snowball sampling and regression were used to collect and process the data. The results of the analysis show that together, all the independent variables have an effect of 56.9% (p<.01) on Instagram addiction. Partially, only negative affectivity (a type D personality factor) does not affect Instagram addiction (β=0.078, p>.05), which means that such addiction is strongly influenced by a combination of external and internal factors. The study illustrates that individuals who have difficulty building social relationships in the real world due to negative self-esteem try to connect with others through social media such as Instagram.